2015
DOI: 10.5194/bg-12-1865-2015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-isotope labelling of organic matter by diffusion of <sup>2</sup>H/<sup>18</sup>O-H<sub>2</sub>O vapour and <sup>13</sup>C-CO<sub>2</sub> into the leaves and its distribution within the plant

Abstract: Abstract. Isotope labelling is a powerful tool to study elemental cycling within terrestrial ecosystems. Here we describe a new multi-isotope technique to label organic matter (OM).We exposed poplars (Populus deltoides × nigra) for 14 days to an atmosphere enriched in 13 CO 2 and depleted in 2 H 18 2 O. After 1 week, the water-soluble leaf OM (δ 13 C = 1346 ± 162 ‰) and the leaf water were strongly labelled (δ 18 O = −63 ± 8, δ 2 H = −156 ± 15 ‰). The leaf water isotopic composition was between the atmospheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The soil water is the source of the two elements and their isotopes, and its uptake by the roots does not cause fractionation of both isotope compositions (White et al, 1985;Ehleringer and Dawson 1992;Dawson and Ehleringer 1993;Lin and Sternberg 1993). Evapotranspiration in the leaves causes enrichment in similar extent of the two heavy isotopes (Flanagan et al, 1991;Yakir 1992;McCarroll and Loader 2004;Studer et al, 2015), thus we can conclude that this does not cause the difference of δ 2 H between the two species but leaving the δ 18 O in the two species unchanged (Figure 2). The difference will FIGURE 4 | Isotopes in cellulose of living trees of 21 different species collected at the Bern Botanical Garden.…”
Section: Discussionmentioning
confidence: 86%
“…The soil water is the source of the two elements and their isotopes, and its uptake by the roots does not cause fractionation of both isotope compositions (White et al, 1985;Ehleringer and Dawson 1992;Dawson and Ehleringer 1993;Lin and Sternberg 1993). Evapotranspiration in the leaves causes enrichment in similar extent of the two heavy isotopes (Flanagan et al, 1991;Yakir 1992;McCarroll and Loader 2004;Studer et al, 2015), thus we can conclude that this does not cause the difference of δ 2 H between the two species but leaving the δ 18 O in the two species unchanged (Figure 2). The difference will FIGURE 4 | Isotopes in cellulose of living trees of 21 different species collected at the Bern Botanical Garden.…”
Section: Discussionmentioning
confidence: 86%
“…But in most cases, the allelopathic substances secreted by indigenous plants are mainly absorbed and utilized by the roots of invasive weeds and participate in cellular metabolic processes to inhibit their growth and development (Cheng and Cheng 2015). The distribution of the atom percent excess (APE) in different parts of A. philoxeroides was different, leaf > root > stem, and plant roots and stems produced more lignin and cellulose, which reduced the synthesis and utilization of allelopathic substances; it also related to the transport of the phloem of the stem, and A. philoxeroides enhanced photosynthesis in order to resist the stress damage of allelopathic substances, which led to the accumulation of more 13 C photosynthetic products in the leaf part (Studer et al 2015). The distribution of 13 C in the different parts of A. philoxeroides showed that the distribution of allelopathic substances absorbed by the plant in roots, stems and leaves was linked to the allelopathic inhibition of morphological characteristics (stem length, root length, node number, leaf number and leaf area).…”
Section: Discussionmentioning
confidence: 99%
“…The δ 13 C of water-soluble organic matter (WSOM) in leaves instead of bulk leaves was determined to represent the carbon isotope signals of photosynthates. Leaf WSOM has a high turnover rate [36][37][38] and mainly includes soluble carbohydrates, the hydrolysates of starch, and amino acids [39,40]. The extraction of WSOM referred to the protocols of [41].…”
Section: Determination Of Carbon Isotope Compositionmentioning
confidence: 99%